Disability, Self-Representation, and Care - T.J. Buttgereit (Feminist Philosophy Quarterly)
In this paper, I examine the implications that the often-used slogan of disability rights, “Nothing about us without us,” has for our understanding of disability identity. I argue that externally labeling a person as disabled violates the principle of self-representation that is at the core of commitment to disability justice. But this concept of self-representation is complicated when we consider those deemed disabled who are incapable of communicating or perhaps even forming a disability identity. With these individuals in mind, I ask, How can self-representation be violated when a person is incapable of forming their own identity? What if external labeling is necessary for caregivers to provide care to their charges? In raising these questions, I seek to highlight how cases of noncommunicative individuals challenge us to rearticulate the meaning of self-identification and recognize the injustice of violating it, even when other obligations to them demand that we do so.